Gejala Inbreeding dalam Penangkaran Satwa Liar - Machmud Thohari (Department of Forest Resources Conservation and Ecotourism - IPB University, 1987)
Captive breeding of some endangered wildlife species is very important, because the extinction of small population is almost inevitable, therefore, the genetic aspects of this breeding program should be made top priority to be observed. The small population size of any species tend to increasethe degradation degree of heterozygosity as a consequence of inbreeding. Genetic variation and the degree of heterozygosity of natural wildlife population are higherthan those of inbred population (in captive breeding) of the same species.Some inbreeding depression in small closed population as well as in captive animals are describedin this paper, e.g. viability depression, fecundity depression, sex ratio depression. To enhance the survival of a species in captive breeding, some strategies are suggested to becarried out, e.g. to avoid starting a population with animals which are already inbred, to prevent starting a population with related animals.